Effect of Myogenous Temporomandibular Joint Disorders on Cervical Range of Motion: A Prospective Study - Junaid Ahmed; Mandovi Nath; Nanditha Sujir; Nandita Shenoy; Ravikiran Ongole; Almas Binnal (Wolters Kluwer Medknow Publications, 2021)
Introduction: Temporomandibular joint disorders (TMDs) involve abnormalities of either the disc or associated muscular structure. Evidence continues to accumulate regarding the untreated diseases of stomatognathic system, in particular, malocclusion and TMDs, which eventually carry a risk of development of postural disorders. The present study was undertaken to assess the correlation between TMDs and altered cervical range of motion and to review its association with the myogenous causes of TMD. Materials and Methods: A total of 80 patients were recruited and were divided into two groups; those diagnosed with TMDs were classified as cases and those who did not suffer from TMDs and/or cervical spine anomalies were classified as controls. Patients reporting with a positive history of painful joints and muscles were examined and were later referred to the department of physiotherapy, where the cervical range of motion was assessed using Baseline® bubble inclinometer. Cervical range of motion in healthy patients was compared with those affected with TMDs using posthoc Tukey test. Results: There was a significant difference in the values for range of motion and was found to be considerably restricted among the TMD subjects. Disability for the range of motion was statistically significant with a P-value of <0.001 for tests of active flexion, passive flexion, left active flexion, and left passive flexion in patients with myogenous TMDs. Conclusion: TMDs were found to be a significant factor in the occurrence of an impaired cervical range of motion.